World economic development : 1979 and beyond - Kahn, Herman; The Hudson Institute (Boulder, Colorado : Westview Press, 1979)
World Economic Development contains eight chapters and an appendix. Chapter 1, the big picture-and some details; Chapter 2, economic growth: contexts, scenarios, images focus on various growth projections, world population and income distributions, and levels of development which may occur in the future. In the consideration of the pros and cons of economic growth, Kahn admits that exponential growth is an impossible situation, but that the steady-state now is equally improbable. He then lays out possible alternatives he believes are before us. Chapter 3 cultural change and economic growth: the emergence of the fourteen new emphases examines; Chapter 4, a speculative overview of the current situation which traces the basic socioeconomic periods of the twentieth century with the aid of business cycle analysis; Chapter 5, Growing Pains: The Emerging Super-Industrial Economy, Malaise, and Inflation; Chapter 6,two and one-half heroes of development: South Korea, Taiwan, and Japan; Chapter 7, more on the Rich, the Middle Income, and the Poor Countries, surveys some of the successes of industrialized nations and some of the prospects of developing nations; and Chapter 8 ("Recommendations, Observations, and Parting Polemics.
Includes bibliographical references and index.
lje 26/09/2018
Loans
Keywords: Economic development; Economic forecasting